PENGARUH METODE SIMULASI PERSIDANGAN TERHADAP PENINGKATAN KESADARAN HUKUM SISWA DI SMA ISLAM TERPADU AL FITYAH PEKANBARU - Amri, Amri Suryanto; Ofianto, Ofianto; Mulyani, Fini Fajri (Universitas Negeri Medan, 2024)
Abstract: This research aims to find out whether there is an influence of the trial simulation method on increasing the legal basics of students at the Al Fityah Pekanbaru Islamic Integrated High School. This research was motivated by students not understanding the impact of behavior that does not comply with legal regulations and providing lessons on social life. In this trial simulation method, students experience first-hand experience as a judge, prosecutor, lawyer and defendant. The formulation of the problem in this research is what is the influence of the trial simulation method on increasing the legal basics of students at Al Fityah Pekanbaru Islamic Integrated High School. The population of this study was all students of Al Fityah Pekanbaru Integrated Islamic High School, totaling 186 students. The number of students used as samples in the research was 41, consisting of all class XII students. The data collection technique uses the product moment correlation test. The results of research on the influence of the trial simulation method on increasing the legal foundation of students at Al Fityah Pekanbaru Islamic Integrated High School are at a